Analytical QbD-based systematic bioanalytical HPLC method development for estimation of quercetin dihydrate. Issue 10 (15th June 2017) - Sandhu, Premjeet Singh; Beg, Sarwar; Kumar, Rajendra; Katare, O. P.; Singh, Bhupinder
ABSTRACT: The current work entails development of rapid, sensitive, and inexpensive high-performance liquid chromatographic method of quercetin dihydrate using the quality by design approach. Quality target method profile was defined and critical analytical attributes (CAAs) were earmarked. Chromatographic separation was accomplished on a C18 column using acetonitrile and ammonium acetate buffer (35:65) %v/v (containing 0.1% acetic acid, pH 3.5) as mobile phase at 0.7 mL/min flow rate with UV detector at 237 nm. Screening studies using fractional factorial design revealed that organic modifier, injection volume, column temperature, and buffer strength have significant influence on method CAAs, namely, peak area, retention time, and peak tailing. The critical method parameters were systematically optimized using Box–Behnken design. Response surface mapping was used along with numerical optimization and desirability function for identifying the optimal chromatographic conditions. Linearity was observed in the drug concentration ranging between 2 and 50 µg/mL. Accuracy analysis revealed mean % recovery between 93.6 and 96.2%, while precision study revealed mean % recovery between 93.7 and 96.5%. Limits of detection and quantification of the developed method were found to be 12.1 and 36.6 ng/mL. Overall, the studies construed successful development of chromatographic method of quercetin with enhanced method performance. GRAPHICAL ABSTRACT: